Madame Bovary : costumbres de provincia - Flaubert, Gustave, 1821-1880; Vargas Llosa, Mario, 1936-; Armiño, Mauro; Flaubert, Gustave, 1821-1880. (Madrid : Siruela, 2014)
Emma Bovary, bored by her provincial life, is drawn to a more sophisticated world that will demand a terrible price.
Online resource; title from ePub title page (Digitalia, viewed March 25, 2016)
Keywords: Physicians' spouses -- Fiction; Adultery -- Fiction; Suicide victims -- Fiction; Middle class -- Fiction; France -- Fiction; Electronic books